Integrative taxonomy clarifies species limits in the hitherto monotypic passion‐vine butterfly genera Agraulis and Dryas (Lepidoptera, Nymphalidae, Heliconiinae). (15th October 2021) - Núñez, Rayner; Willmott, Keith R.; Álvarez, Yosiel; Genaro, Julio A.; Pérez‐Asso, Antonio R.; Quejereta, Marina; Turner, Thomas; Miller, Jacqueline Y.; Brévignon, Christian; Lamas, Gerardo; Hausmann, Axel
Abstract: The Heliconiini genera Agraulis and Dryas are widely distributed throughout the Neotropics and into adjacent temperate regions, and although they are currently treated as monotypic, both show significant geographic phenotypic variation. In this work, we employ six genetic markers (4199 bp), two mitochondrial and four nuclear, to perform coalescent species delimitation analyses in Bayesian Phylogenetics and Phylogeography (BPP) and in integrated BPP (iBPP), the latter also includes linear measurements and wings landmarks. We also analyze cytochrome c oxidase I (COI) barcode sequences for each genus using genetic distances, haplotype networks and a character‐based approach. Based on the model testing results, complemented with data from previous studies, we performed morphometric analyses to compare fore and hindwing size, aspect ratio and shape among the new species. In addition, we compared the forewing spot pattern of hypothesizes species using the r package patternize and, for Dryas, compared the colour patterns of mature larvae. Model testing of the molecular species delimitation outputs favoured a seven species hypothesis for Agraulis and a four species hypothesis for Dryas . Average distances among COI barcode sequences of these groups were from 1.09 to 5.81% in Agraulis and from 1.09 to 3.44% in Dryas . Within‐group distances ranged from 0 to 1.11% and between 0 and 2.43%, respectively. NeighborNet haplotype networks showed that all but one of the species are monophyletic, and the character‐based approach found exclusive diagnostic positions for most species, while the rest can be recognized by unique combinations of the 44 informative nucleotide positions analysed. Morphometric analysis supported all species of Agraulis and Dryas based on wing shape, and also in several cases on wing sizes and aspect ratio (hindwing length–forewing length), including A . v . galapagensis, which was absent from the molecular study. The analysis of the forewing spot pattern also revealed differences among most species hypothesis. The colour pattern of the last instar larva is also diagnostic for each Dryas species hypothesis. Locality data for species in both genera show that most of them are allopatric albeit a few have contact zones being parapatric at some locations. Based on the observed genetic differences, which covary with morphology and geographical distribution, we recommend the recognition of eight species of Agraulis : A. incarnata, A. vanillae, A. forbesi new status, A. insularis reinstated status, A. maculosa new status, A. lucina reinstated status, A. galapagensis new status and one undescribed species, and four species of Dryas : D. iulia, D. dominicana revised status, D. lucia revised status and D. alcionea reinstated status . Further work is needed to investigate, which selective forces have led to the current configurations of venation and wing shape, the probable gene flow among species with a focus on Agraulis and gather more data on species ecology. LSIDurn: lsid: zoobank.org : pub: 9E8C9F6E‐91C3‐4FB2‐804D‐1A9C4BD2EABB. Abstract : Molecular, morphometric and forewing pattern analyses support several species in the hitherto monotypic passion‐vine butterfly genera Agraulis and Dryas . All data analysed co‐vary geographically with colour pattern of Dryas mature larvae also varying accordingly. While Dryas species are fully allopatric, most adjacent Agraulis species have contact zones. Agraulis and Dryas populations face a broad array of ecological conditions across their distributions from the arid Pacific coast to the Amazon basin and the West Indies, which likely have influenced speciation processes.